Nanostructured SERS substrates produced by nanosphere lithography and plastic deformation through direct peel-off on soft matter. (24th March 2016) - Wang, Tzyy-Jiann; Hsu, Kai-Chieh; Liu, Yi-Cheng; Lai, Chih-Hsien; Chiang, Hai-Pang
Abstract: We present a novel fragmented-film surface-enhanced Raman scattering (SERS) substrate produced by nanosphere lithography and direct peel-off for SERS efficacy enhancement. The 2D hexagonally close-packed polystyrene nanospheres on the polydimethylsilozane (PDMS) substrate are covered with silver film and then directly peeled off using sticky tape. During the peel-off process, the pulling force induces the stretch and contraction of the PDMS substrate and causes fracture of the 2D triangular silver film. Under laser excitation, a stronger localized electric field is induced in the smaller cracks and enhances the SERS intensity. The origin of this SERS enhancement is confirmed by numerical simulation using the finite element method and substrate annealing to smoothen the cracks. For the case using nanospheres with a diameter of 740 nm, an enhancement factor 6.5 × 10 6 can be achieved. The proposed fragmented-film SERS substrate gains 1.8 and 2.6 times larger Raman intensity at the 1358 cm −1 SERS peak than those using pyramidal silver islands and silver nanoshell array. The proposed SERS substrate has the features of easy fabrication, low production cost, short fabrication time and high enhancement factor.